Effects of Self-Protective Techniques on Independent Travel for Blind Students - Qurrotu'aini, Nabilah; Meiyani, Neni (Department of Special Education, 2024)
The problem in this research is the low skills of a blind student in traveling independently around the school environment. Researchers use self-protective techniques to improve blind student independent travel skills in grade 5th. The purpose of this research is to get data about the effects of self-protective techniques on the skills of independent travel for blind students. This research uses the experiment method with Single Subject Research (SSR) design, with A-B-A research design. Based on the research result, there is a positive effect on the use of self-protective techniques towards increasing the skills of independent travel of 5th-grade blind students. Therefore, it is recommended that orientation and mobility teachers use self-protective techniques as one of the orientation and mobility learning techniques that can improve independent travel skills among blind students.